2013
DOI: 10.1111/sji.12109
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐Infiltrating FoxP3+ and IL‐17‐Producing T Cells Affect the Progression and Prognosis of Gallbladder Carcinoma after Surgery

Abstract: Tumour-infiltrating lymphocytes (TILs) have been found to play crucial roles in a series of cancers. However, the impact of these cells on gallbladder carcinoma (GBC) remains poorly understood. In this study, we examined infiltrating FoxP3+, IL-17+, CD4+ and CD8+ cells by immunohistochemistry in specimens of 104 patients with GBC and evaluated the association of these cells with clinicopathological features and prognosis. The number of FoxP3+ cells was increased in a stepwise manner from CC to GA and GBC (GA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Moreover, it is reported that Th17 and Treg frequently colocalize at the same anatomic compartments and mutually promote each other's generation and function . We observed the infiltration of Treg and IL17 producing cells in the tumor environment of GBC patients which corroborate the earlier observations in GBC patients reported by Zhang et al . This suggests that although the ratios of Tγδ17/Treg, Th17/Treg and Tc17/Treg were increased in GBC patients, IL17 producing cells and Tregs may act cooperatively and eventually contribute to the poor survival observed in GBC patients.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it is reported that Th17 and Treg frequently colocalize at the same anatomic compartments and mutually promote each other's generation and function . We observed the infiltration of Treg and IL17 producing cells in the tumor environment of GBC patients which corroborate the earlier observations in GBC patients reported by Zhang et al . This suggests that although the ratios of Tγδ17/Treg, Th17/Treg and Tc17/Treg were increased in GBC patients, IL17 producing cells and Tregs may act cooperatively and eventually contribute to the poor survival observed in GBC patients.…”
Section: Discussionsupporting
confidence: 91%
“…CLL D chronic lymphocytic leukemia; AC D adenocarcinoma; CRC D colorectal carcinoma; HCC D hepatocellular carcinoma; NA D not applicable or not mentioned in the article; NSCLC D non-small cell lung carcinoma. 15,16,[18][19][20]30,37,[40][41][42][43][44][45][46][47][48][49][50] Five studies reported on a correlation between a high number of IL-17 C cells and improved survival. 21,28,29,51,52 It is important to note that in two of these five studies, the IL-17 C cells were scored in areas with the densest lymphocytic infiltrate, one of which was on pancreatic ductal adenocarcinoma patients who had received immunotherapy (the correlation between IL-17 and survival was based on 12 patients).…”
Section: Study Design and Selection Criteriamentioning
confidence: 99%
“…As shown in Fig 2.A, the relevance between high level of IL-17 + cells and histological grade (poor differentiation versus (vs.) well/moderate differentiation) was evaluated in 14 studies including head and neck cancers (HNC) (n = 2) [38,39], breast cancer (n = 1) [17], non-small-cell lung cancer (NSCLC) (n = 2) [40,41] and cancers of digestive system (n = 9) [16,20,28,[42][43][44][45][46][47], with 1645 patients. Results showed no statistical significance was found between high level of IL-17 + cells and histological grade (RR = 1.10, 95% CI [0.90, 1.34]).…”
Section: Il-17 + Cells and Histological Gradementioning
confidence: 99%
“…The association between high IL-17 + cells and lymph node metastasis was explored in 9 studies with 1074 patients [17,20,38,[42][43][44][45][46]48] (Fig 2.B). RR for the relevant 9 studies was 0.97 (95% CI [0.81, 1.15]), indicating the high IL-17 + cells within tumor tissues had no significant influence on lymph node status.…”
Section: Il-17 + Cells and Lymph Node Metastasismentioning
confidence: 99%
See 1 more Smart Citation